Pengaruh Kualitas Penerapan Good Corporate Governance dan Risiko Kredit terhadap Profitabilitas Perbankan Asing di Indonesia - Giavinny Giavinny; Gracia S Ugut (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This article or article aims to analyze the effect of the quality of the implementation of Good Corporate Governance and credit risk on foreign banking profit in Indonesia. The data collected through observations from 2016 to 2020 collected from the annual good corporate governance report and annual report published through the website of each bank and analyzed quantitatively using secondary data with purposive sampling, then the sample of this study amounted to 23 foreign banks. The analytical method used to test the hypothesis in this study is a multiple linear regression analysis using Eviews version 10. The review concluded that simultaneously the Quality of Implementation of Good Corporate Governance (GCG) and credit risk (NPL) has a simultaneous effect on profitability (ROA). Partially, credit risk variable (NPL) are negative and significant to profitability (ROA), while good corporate governance (GCG) has a negative but insignificant effect on profitability (ROA).